Frequency of MRSA in Diabetic Foot Infections a Prospective Multi Centre Study - Rab Nawaz, Khalid Usman, Sahibzada Imtiaz Ahmad, Saleh Ahmad, Kifayat Ali, Tahir Ghafar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diabetic foot infection are a widely recognized side effect of diabetic patients who are frequently admitted and even their limbs are amputated. MRSA has become an important cause of Diabetic foot infection and makes the treatment difficult because of its resistance pattern. Estimation of the frequency and risk factors are important in providing empirical therapy to patients with an aim of improving their outcomes. Objectives: To find the prevalence of MRSA cases in diabetic foot and to evaluate the clinical and demographic characteristic related to the MRSA positive cases. Study design: A Prospective Multi Centers Study. Place and Duration of Study: Department of Endocrinology, MTI-HMC Peshawar; Timergara Teaching Hospital, Timergara and the District Headquarter Hospital, Dir Upper from July 2022 to Dec 2022. Methods: 100 clinically identified patients with foot infection due to diabetes was then done. Microbial analysis was carried out by the use of wound swabs. The identification of MRSA was carried out by conventional microbiology methods such as the cefoxitin disc diffusion. Demographic-related data, length of diabetes, grade of ulcers, and use of antibiotics were captured. The SPSS version 25 was used to analyze statistics. The statistics were calculated as mean age, standard deviation, and p-values to get the statistical significance. Results: Out of 100 patients were positive to MRSA. The average age of the group (patients with MRSA infection) was 59.3 + 9.8 years where 55.2 + 10.1 years was observed in the group without MRSA infection (p = 0.04). The previous application of antibiotics and duration of ulcer were considerably higher in MRSA-positive patients (p < 0.05). There were 2.3 males to every 1 female. MRSA-positive patients had more advanced ulcer. Mean length of stay in this group was 12.7 +- 4.2 days as well. Conclusion: Methicillin-resistant Staphylococcus aureus (MRSA) represents a significant pathogen in diabetic foot infections, particularly among patients with chronic ulcers, prior antibiotic exposure, and advanced ulcer grades. Its prevalence poses a clinical challenge due to its resistance profile and associated complications. Early identification and the initiation of appropriate empirical therapy, even if initially delayed, can contribute to improved clinical outcomes and reduced hospital stay. To mitigate the impact of MRSA within diabetic populations, consistent microbiological surveillance and stringent implementation of antibiotic stewardship programs are imperative. Keywords: MRSA, diabetic foot, infection, prevalence